Using Lyα Absorption to Measure the Intensity and Variability of z ∼ 2.4 Ultraviolet Background Light - Laurel H. Weiss; Karl Gebhardt; Dustin Davis; Erin Mentuch Cooper; Maja Lujan Niemeyer; Mahdi Qezlou; Mahan Mirza Khanlari; Robin Ciardullo; Daniel Farrow; Eric Gawiser; Simon Gazagnes; Caryl Gronwall; et al. (The Astrophysical Journal)
We present measurements of z  ∼ 2.4 ultraviolet (UV) background light using Ly α absorption from galaxies at z  ∼ 2–3 in the Hobby–Eberly Telescope Dark Energy Experiment (HETDEX) database. Thanks to the wide area of this survey, we also measure the variability of this light across the sky. The data suggest an asymmetric geometry where integrated UV light from background galaxies is absorbed by H i within the halo of a foreground galaxy, in a configuration similar to damped Ly α systems. Using stacking analyses of over 400,000 HETDEX LAE spectra, we argue that this background absorption is detectable in our data. We also argue that the absorption signal becomes negative due to HETDEX’s sky-subtraction procedure. The amount that the absorption is oversubtracted is representative of the z  ∼ 2.4 UV contribution to the overall extragalactic background light (EBL) at Ly α . Using this method, we determine an average intensity (in νJ _ν units) of 12.9 ± 3.7 nW m ^−2 sr ^−1 at a median observed wavelength of 4134 Å, or a rest-frame UV background intensity of 508 ± 145 nW m ^−2 sr ^−1 at z  ∼ 2.4. We find that this flux varies significantly depending on the density of galaxies in the field of observation. Our estimates are consistent with direct measurements of the overall EBL.